Skrining Penyakit Tidak Menular Pada Masyarakat Condongcatur Depok Sleman - Chentia Misse Issabella; Febry Heldayasari Prabandari (J.Abdimas: Community Health, 2021)
Non-communicable diseases (NCDs) are diseases that are not transmitted and cannot be transmitted to other people by any form of contact that can cause death and kill 60% of all deaths globally and prevalence data in developing countries reaches 80%. Non-communicable diseases, especially cardiovascular diseases, cancer, chronic respiratory diseases, and diabetes mellitus are major threats to human health and development today. This community service aims to detect non-communicable diseases, namely screening for blood pressure, blood sugar levels (GDS), cholesterol, and uric acid, in the Padukuhan Pikgondang community, Condongcatur Village, Depok, Sleman, Yogyakarta. The types of activities carried out are in the form of health education, blood pressure checks, cholesterol levels, temporary blood sugar and uric acid. Blood pressure was measured using a sphygnomanometer and a stethoscope while the analysis of cholesterol, blood sugar and uric acid used a digital checking device. In this community service, screening and early detection of risk factors for non-communicable diseases have been carried out on 46 respondents, including 28 men and 18 women. The results of the examination showed that the average systolic blood pressure for men was 135 mmHg, while for women was 140 mmHg. The average diastolic blood pressure for men is 80 mmHg and women 80 mmHg and it can be seen that most residents have high blood pressure of 86.96% and 58.70% of residents have normal cholesterol levels (<200 mg/dl). The results of the GDS examination were 80.43% of residents had normal sugar levels (<200 mg/dl) and 73.91% of residents had normal uric acid levels (<7mg/dl). With the results of this screening, further follow-up will be obtained from the Depok II Public Health Center and can maximize the use of Posyandu as a place for screening non-communicable diseases and seek counseling and education about these non-communicable diseases.